2022
DOI: 10.1109/twc.2021.3095174
|View full text |Cite
|
Sign up to set email alerts
|

Maximizing the Geometric Mean of User-Rates to Improve Rate-Fairness: Proper vs. Improper Gaussian Signaling

Abstract: This papers considers a reconfigurable intelligent surface (RIS)-aided network, which relies on a multiple antenna array aided base station (BS) and a RIS for serving multiple single antenna downlink users. To provide reliable links to all users over the same bandwidth and same time-slot, the paper proposes the joint design of linear transmit beamformers and the programmable reflecting coefficients of an IRS to maximize the geometric mean (GM) of the users' rates. A new computationally efficient alternating de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 39 publications
0
54
0
Order By: Relevance
“…IGS was employed as an interference-management technique for the first time in [8], where the authors showed that IGS can increase the degrees-of-freedom (DoF) of the 3-user IC. In the last decade, IGS has been applied to various interference-limited systems, showing that it can increase the spectral and energy efficiency of such systems with TIN [9]- [31]. For instance, the papers [11]- [14] showed that IGS can improve the rate and/or energy efficiency (EE) of the secondary user in cognitive radio systems.…”
Section: A Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…IGS was employed as an interference-management technique for the first time in [8], where the authors showed that IGS can increase the degrees-of-freedom (DoF) of the 3-user IC. In the last decade, IGS has been applied to various interference-limited systems, showing that it can increase the spectral and energy efficiency of such systems with TIN [9]- [31]. For instance, the papers [11]- [14] showed that IGS can improve the rate and/or energy efficiency (EE) of the secondary user in cognitive radio systems.…”
Section: A Related Workmentioning
confidence: 99%
“…How to solve the aforementioned challenges remains an open question in RIS-assisted systems. RIS is an emerging technology, which has been shown to be able to improve the spectral and energy efficiency of various systems [1]- [4], [31], [36]- [46]. For example, the papers [37]- [39], [46] considered various performance metrics such as global energy efficiency (GEE), sum rate, minimum SINR and showed that RIS can improve the spectral and energy efficiency of a single-cell BC with a multi-antenna BS and multiple single-antenna users.…”
Section: A Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…C. Algorithm Algorithm 1 provides the pseudo-code for the proposed steep descent computational procedure of (7) as the iterations ( 22) and (32) seek a descent direction by seeking a better feasible point for the nonconvex problem (7).…”
Section: B Programmable Reflecting Elements' Descent Iterationmentioning
confidence: 99%
“…Contributing to the general line of work outlined above, we propose in this article a novel joint AP access configuration, power allocation, and beamforming algorithm for dynamic TDD-based CF-mMIMO systems, which aims at a reasonable optimized solution that balances system throughput and user fairness. To this end, we consider the maximization of the geometric mean of the UEs' throughput so as to maximize the total throughput utility while reducing the variance among the UE's achievable throughputs, which is motivated by recent studies such as those in [26], [27]. The resulting maximization problem involving the geometric mean objective function is highly intractable, due not only to the non-convexity of the signal-to-interference-and-noise ratio (SINR) expression, but also to the binary (discrete) feasibility set of DL/UL AP access configuration.…”
Section: Introductionmentioning
confidence: 99%